Diagnosa Penyakit Kulit (Dermatitis) menggunakan Metode Certainty Factor - Widya Natasya; Achmad Fauzi; Victor Maruli Pakpahan (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Dermatitis is an inflammatory skin disease that is accompanied by itchy skin. It occurs in infants, and gets better in adolescence, but some cases can persist for a long time or even develop the disease in adulthood. In general, if you have this skin disease, you should see a skin specialist for a consultation. However, skin specialists are not always at the hospital, making it difficult for patients to arrange appointments to meet or consult. Therefore, the hospital needs to have an additional system that can help facilitate the medical team to detect the type of dermatitis disease based on symptoms (blistering skin, redness of the skin, scaly and dry skin, dark skin, blistering skin, cracked skin that is present in the disease, atopic dermatitis, contact dermatitis, seberoic dermatitis, nummular dermatitis, and intertriginous dermatitis and get handling and understanding of dermatitis disease using the certainty factor method. From the analysis carried out, the results of the diagnosis of the selected symptoms are obtained, the most accurate diagnosis is Atopic Dermatitis 98% with the treatment given, namely Corticosteroids and Antihistamines to patients.